Mobility, bioavailability, and toxic effects of cadmium in soil samples - Prokop, Z; Cupr, P; Zlevorova-Zlamalikova, V; Komarek, J; Dusek, L; Holoubek, I (Environmental research, 2003)
Total concentration is not a reliable indicator of metal mobility or bioavailability in soils. The physicochemical form determines the behavior of metals in soils and hence the toxicity toward terrestrial biota. The main objectives of this study were the application and comparison of three approaches for the evaluation of cadmium behavior in soil samples. The mobility and bioavailability of cadmium in five selected soil samples were evaluated using equilibrium speciation (Windermere humic aqueous model (WHAM)), extraction procedures (Milli-Q water, DMSO, and DTPA), and a number of bioassays (Microtox, growth inhibition test, contact toxicity test, and respiration). The mobility, represented by the water-extractable fraction, corresponded well with the amount of cadmium in the soil solution, calculated using the WHAM (r(2)=0.96, P<0.001). The results of the ecotoxicological evaluation, which represent the bioavailable fraction of cadmium, correlated well with DTPA extractability and also with the concentration of free cadmium ion, which is recognized as the most bioavailable metal form. The results of the WHAM as well as the results of extraction experiments showed a strong binding of cadmium to organic matter and a weak sorption of cadmium to clay minerals.
Keywords: Clay; adsorpce; huminové látky; látky znečišťující půdu; testy toxicity; biologická dostupnost; teoretické modely; jíl; Models, Theoretical; Soil Pollutants; Cadmium; Humic Substances; chemické techniky analytické; populační dynamika; kadmium; Bacillus cereus; Pseudomonas putida; silikáty hliníku; Aluminum Silicates; Solubility; Population Dynamics; Chemistry Techniques, Analytical; rozpustnost; Toxicity Tests; Adsorption; Biological Availability